A View on Pathogenesis of ≪Vicious Cancer Progression Cycle≫ - Schwartsburd, Polina (Frontiers in Oncology, 2020)
Similar to parasites, cancer cells depend on their hosts for their sustenance and proliferation, exploiting the organism’s resources, and thereby impairing the host’s health. For unrestrained growth, these cells must acquire the capacity to instruct the host to grow new blood vessels to constantly provide them with host glucose. What pathological mechanism is responsible for this activity? According to the current analysis, tumor cells can supply themselves with host glucose by creating a glucose-delivering vicious cycle presented as the feedback model in Fig.1. This model contributes to better understanding the metabolic basis of adverse cancer effects on the organism and identifying the potential therapeutic targets. In summary, the presented analysis describes a possibility of clinical inhibition of the vicious cycle activity to prevent or improve the catabolic host state associated with cancer cell growth and progression.